Perfil e motivações dos estudantes participantes do "Programa de Mobilidade Discente Internacional para a Graduação" da UFMG - Viviane Coelho Caldeira Ramos (2009)
The object of this dissertation is the Programa de Mobilidade Discente Internacional para a Graduação (Undergraduate Exchange Program) of UFMG, through which the undergraduate students of the university have the opportunity to study for a semester in a partner university abroad. In 2008, 186 students participated in the program, coordinated by Diretoria de Relações Internacionais (DRI- Office of International Relations) of UFMG. The work was guided by two basic questions: who are those exchange students? Why have they decided to partake in the program? To answer these questions, different research instruments were used: a) analysis of DRI documents; b) observation of selection interviews; c) secondary data collection about the exchange students of 2008 (N=177); d) questionnaire application; e) semi-directive interviews with a smaller number of exchange students (N=41). The results showed that the typical exchange student belongs to the middle classes. Nonetheless, there was a number higher than expected of students from low-income backgrounds that participated in the program. This is probably due to the financial support given by an institutional fund. Apart from that, it was showed that the exchange students have built, throughout their lives, a mobility capital and successful academic curriculum vitae that differentiates them from the average student of UFMG. Regarding their motivations to participate in the exchange program, the students interviewed expect that their study period abroad fulfills a double function. On the one hand, they aspire the development of instrumental competencies, as the improvement of their foreign language competence. On the other hand, they also have expectations about the formation of personal dispositions of tolerance, autonomy, etc. Competencies and dispositions that, they believe, will become future trumps in the school and work markets.